2016
DOI: 10.1016/j.mrfmmm.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Increased MTHFR promoter methylation in mothers of Down syndrome individuals

Abstract: Despite that advanced maternal age at conception represents the major risk factor for the birth of a child with Down syndrome (DS), most of DS babies are born from women aging less than 35 years. Studies performed in peripheral lymphocytes of those women revealed several markers of global genome instability, including an increased frequency of micronuclei, shorter telomeres and impaired global DNA methylation. Furthermore, young mothers of DS individuals (MDS) are at increased risk to develop dementia later in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…In the current study, by comparison to control mothers, young mothers with DS children were more likely to be from rural areas (60%) than urban areas (40%) and of a low socioeconomic status (62%) rather than a high socioeconomic status (38%), and these data match with a previous report from India [25]. These findings may be related to environmental and/or nutritional factors such as folic acid deficiency or pollution by pesticides [26,27]. The poverty of proper prenatal diagnosis and lack of well-established health care services coupled with low education appears to be another factor that may cause higher DS birth rate in rural rather than urban areas [13,28].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the current study, by comparison to control mothers, young mothers with DS children were more likely to be from rural areas (60%) than urban areas (40%) and of a low socioeconomic status (62%) rather than a high socioeconomic status (38%), and these data match with a previous report from India [25]. These findings may be related to environmental and/or nutritional factors such as folic acid deficiency or pollution by pesticides [26,27]. The poverty of proper prenatal diagnosis and lack of well-established health care services coupled with low education appears to be another factor that may cause higher DS birth rate in rural rather than urban areas [13,28].…”
Section: Discussionsupporting
confidence: 88%
“…Studies have found an association between genome instability and young mothers who had at least one DS child. The genome instability is being indicated by biomarkers such as increased frequency of micronuclei [31], shorter telomeres [32], and premature centromere separation [33], in addition to impaired DNA methylation as a result of folate pathway genetic polymorphism, particularly the methylenetetrahydrofolate reductase (MTHFR) gene [26]. These studies suggested that young mothers of DS children are considered "biologically older" than mothers of the same age with normal babies.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it was suggested that MTHFR hypermethylation might confer a growth advantage to cancer cells and contribute to the cancer phenotype in tumors of the upper aero-digestive tract [25]. Moreover, MTHFR promoter methylation levels have been correlated with cancer risk factors and with markers of impaired folate metabolism, including tobacco smoking, low circulating folates and vitamin B12, high homocysteine levels, and increased chromosome instability [15,18,26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…However, as far as MTHFR promoter methylation in the blood is concerned, it should be noted that rather than being a specific marker of a given disease, it could represent a more general biomarker of increased genomic instability. For example, some studies suggest a correlation between hyperhomocysteinemia and MTHFR promoter methylation [26]; others have linked MTHFR promoter methylation in blood cells with markers of chromosome damage, such as an increased frequency of micronuclei [27] or alterations of LINE-1 methylation and stability [15], and there is also indication that MTHFR promoter methylation in blood DNA might reflect dietary B-group vitamin deficiency [18,30] or environmental exposure to cancerous agents, such as those deriving from tobacco smoking [15]. Collectively, those studies suggest that increased MTHFR promoter methylation in blood cells might be a more general marker of impaired one-carbon metabolism and genome instability, rather than a specific disease biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…The recent meta-analysis suggested that MTHFR 677T is a major risk factor for DS birth [105], while previous smaller studies did not recognize such risk [106,107]. Studies performed analyzing peripheral lymphocytes of women with DS offspring revealed several markers of global genome instability, including an increased frequency of micronuclei, shorter telomeres, and impaired DNA methylation at MTHFR promoter [108,109]. Hypermethylation of MTHFR promoter may lead to CHD in DS subjects [109].…”
Section: Epigenetic Genetic and Nutrigenomic Risk Factors For Congementioning
confidence: 99%